Consumer Reviews on TikTok and Their Impact on Millennial Saving Decisions - Shagi Aprilia Kurniawan; Tetty Rimenda; Agus Buntoro; R. Elly Mirati (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The purpose of this study is to investigate customer reviews of banking advertisements onTikTok. The current phenomenon is the emergence of formal banking product advertisements on social media such as in Instagram, Twitter or FB. Another phenomenon that appears is the way customers make decisions has also changed. Before making a decision, customers prefer reviews given by customers uploaded on social media, Data collection was collected by survey method. Questionnaires distributed on Instagram. Respondents were screening only for those who had seen a review of a savings product ad on TikTok which consisted of 171 people. The findings show that positive reviews (P-Reviews) and negative reviews (N-Reviews) influence customers' saving decisions. However, our particular finding is that N-Review has a greater influence on customers' saving decisions than P-Review. The product weakness construct is the biggest determinant in deciding to buy a product. This concludes that customers are very careful about product deficiencies. N-Reviews published on social media make customers more careful when buying products because customers don't want to lose money. On the other hand, for a product that is considered good, the volume of (P-Reviews) must be high in order to create a positive impression on customers.